The Effect of the Covid-19 Pandemic on Language Errors in Scientific Texts for IAIN Bone Students - Ahmad, Ahmad; Rijal, Ahsanur; Ramli, Ratu Bulkis (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2021)
The study aims to describe the error of Indonesian done the student at covid-19 pandemic. This research is a descriptive type. The source of the data in this study are the student of IAIN Bone. The instruments used in this research include observation sheets, reading, and note-taking techniques. Analytical techniques used in analyzing data-error language i.e. qualitative data analysis techniques. The results of this research show that there were errors in using Indonesian, which include standard words, phonological, morphological, syntactic, and percentage of the language error diagram. The advice of this research, the lecturer or the teacher can use the results of the analysis on language errors made by students as reflection of learning.